2021
DOI: 10.1002/hbe2.286
|View full text |Cite
|
Sign up to set email alerts
|

Unusual artifacts: Linking parents' STEM background and children's animacy judgments to parent–child play with robots

Abstract: Although prior work has investigated children's judgments of robots' animacy, we take a sociocultural perspective to extend this research by exploring how families' interactions with a robot and parents' STEM background relate to children's understanding of robots. We explored the social context of parent-child goal-directed play with an educational robot and asked whether children's judgments of the robot's animacy were predicted by (a) age, (b) parents' occupation (STEM, non-STEM), (c) parents' level of educ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(13 citation statements)
references
References 33 publications
0
13
0
Order By: Relevance
“…Eight toddlers refused to play with the robot in the playroom, while eleven toddlers interacted with the robot. The remote teleoperated system increased opportunities for grandparent-grandchild interactions and promoted the sharing of [1,20]; At Home Special Education and Family Bonding [6]; Family Co-Learning [2]; Family Dynamics [46] Robot Perceptions [43]; Robot Adoption in Long-Term [4,34,40]; Robot Acceptance [27,39,42] daily life. Motivated by these interactions, grandparents paid special attention to their appearance during video interactions.…”
Section: Robot Interactions That Impact Family Lifementioning
confidence: 99%
See 4 more Smart Citations
“…Eight toddlers refused to play with the robot in the playroom, while eleven toddlers interacted with the robot. The remote teleoperated system increased opportunities for grandparent-grandchild interactions and promoted the sharing of [1,20]; At Home Special Education and Family Bonding [6]; Family Co-Learning [2]; Family Dynamics [46] Robot Perceptions [43]; Robot Adoption in Long-Term [4,34,40]; Robot Acceptance [27,39,42] daily life. Motivated by these interactions, grandparents paid special attention to their appearance during video interactions.…”
Section: Robot Interactions That Impact Family Lifementioning
confidence: 99%
“…For example, new members may join or leave the family system for various reasons (short-term changes: work, vacation, school; long-term changes: birth, death, marriage, divorce). From the literature review, we identified that several family members' characteristics play a significant role in shaping how family members perceive and engage with robots, these include: family routines [40]; parents' STEM backgrounds [43]; dual parent employment and parenting styles [39]; family resilience towards changes in children's health conditions [34]; the spectrum of children's diagnosis and parents physical presence [4]; children's hedonic, social, and utilitarian beliefs [27]; and parents' perceptions towards the agency, intelligence, and expressivity of robots [42].…”
Section: Familymentioning
confidence: 99%
See 3 more Smart Citations